ANALYSIS OF THE DIGITAL SERVICE QUALITY OF THE MYICON+ APPLICATION IN SUPPORTING THE DIGITAL TRANSFORMATION OF PUBLIC SERVICES AT PT PLN ICON PLUS - Whimar Admojo; Sri Kamariyah; Ika Devy pramudiana; Nihayatus Sholichah (International Journal of Multidisciplinary Reseach, 2026)
The digital transformation of public services in Indonesia increasingly requires digital platforms that are not merely available, but also reliable, secure, responsive, and inclusive across the entire service journey. This study analyzes the digital service quality of the MyICON+ application in supporting public service digital transformation at PT PLN Icon Plus using the Electronic Service Quality (E-ServQual) framework, consisting of e-tangibility, reliability, responsiveness, assurance, and empathy. The study employs a descriptive qualitative approach through in-depth interviews, non-participant observation, and documentary analysis of updated 2026 information from official PLN Icon Plus publications, Google Play, Apple App Store, and ICONNET service pages. The findings show that MyICON+ has progressed from a supporting application into a multi-channel service portal available through mobile and web access, with official functions covering complaint reporting, service-status monitoring, product management, billing history, and service information. Recent platform indicators such as more than one million downloads on Google Play, regular application updates, and a 4.1/5 rating from around 6.7 thousand ratings on the App Store indicate broader adoption and active maintenance. Nevertheless, the quality of digital transformation remains partial. Assurance is relatively strong due to institutional credibility, data-encryption claims, and information-security-related certifications, while reliability and responsiveness remain critical because users still report instability, delayed complaint handling, and inconsistent service-status accuracy. The study identifies a reinforced digital-facade phenomenon, in which visible digital access has improved faster than back-end process reliability and human-centered service recovery. The study recommends strengthening back-end infrastructure, harmonizing privacy communication, restructuring SLA monitoring, and developing a role-based digital empathy ecosystem.